2017
DOI: 10.1111/nph.14615
|View full text |Cite
|
Sign up to set email alerts
|

Identification of major loci and genomic regions controlling acid and volatile content in tomato fruit: implications for flavor improvement

Abstract: Plant metabolites are important to world food security due to their roles in crop yield and nutritional quality. Here we report the metabolic profile of 300 tomato accessions (Solanum lycopersicum and related wild species) by quantifying 60 primary and secondary metabolites, including volatile organic compounds, over a period of 2 yr. Metabolite content and genetic inheritance of metabolites varied broadly, both within and between different genetic groups. Using genotype information gained from 10 000 single n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
105
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(113 citation statements)
references
References 97 publications
(157 reference statements)
3
105
0
5
Order By: Relevance
“…Among the QTLs that were conserved are phenylalanine on chromosome 10 and methionine on chromosome 8. By contrast, the first reported GWAS study on primary metabolism in tomato did not reveal 44 candidate loci for fruit metabolic traits (Sauvage et al ., ), and a larger study by the same group (Bauchet et al ., ) did not identify associations with phenylalanine or methionine levels. This observation thus provides further support for the value of such populations.…”
Section: Discussionmentioning
confidence: 85%
“…Among the QTLs that were conserved are phenylalanine on chromosome 10 and methionine on chromosome 8. By contrast, the first reported GWAS study on primary metabolism in tomato did not reveal 44 candidate loci for fruit metabolic traits (Sauvage et al ., ), and a larger study by the same group (Bauchet et al ., ) did not identify associations with phenylalanine or methionine levels. This observation thus provides further support for the value of such populations.…”
Section: Discussionmentioning
confidence: 85%
“…Among them, five and 36 SNPs were also detected as being associated with capsaicin content, and only these reached the FDR threshold for this association. Several GWAS and QTL mapping studies have demonstrated that one locus can control multiple highly correlated traits (Bauchet et al ., ; Ben‐Chaim et al ., ; Crowell et al ., ; Han et al ., ; Wang et al ., ). We detected a high correlation between capsaicin, dihydrocapsaicin and total capsaicinoid contents; therefore, it is possible that some SNPs can affect these traits simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these major mutations, several QTLs controlling fruit size, shape, color intensity, firmness, and composition were mapped. With the development of high throughput metabolome studies, the content of hundreds primary and secondary metabolites was assessed (Carrari et al ., ; Bauchet et al ., ; Tieman et al ., ). Concerning tomato sensory quality, many QTLs for sensory traits were mapped as well as QTLs for volatile organic compounds (Causse et al ., ; Tieman et al ., ) and a few were positionally cloned (Supplementary Table S1).…”
Section: Discovery Of Genetic Variations Underlying Major Traits In Tmentioning
confidence: 98%
“…The genetic control of fruit anti‐nutritional alkaloids was also deciphered (Itkin et al ., ). GWAS studies coupled with mQTL analyses further identified several loci of interest for improving major fruit quality traits such as malic acid content (Ye et al ., ) or aromas (Bauchet et al ., ; Tieman et al ., ). More recently, Zhu et al .…”
Section: Discovery Of Genetic Variations Underlying Major Traits In Tmentioning
confidence: 98%
See 1 more Smart Citation